2002
DOI: 10.1046/j.1365-2168.2002.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of peritoneal blood flow and insufflation pressure during laparoscopy

Abstract: These data suggest that blood flow within the peritoneum is influenced by insufflation with carbon dioxide. It is conceivable that such hyperaemia could increase the propensity for implanted tumour cells to metastasize in these sites following laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
4
18
0
1
Order By: Relevance
“…The current study shows, in accordance with a recent study [2], that insufflation of CO 2 into the abdominal cavity of pigs is associated with a substantial increase in blood flow in the peritoneum. Our findings also support the view that such vasodilation is caused by properties related to CO 2 itself, and not to changed central hemodynamics or activation of neural reflex mechanisms potentially elicited by increased intraabdominal pressure.…”
Section: Discussionsupporting
confidence: 79%
“…The current study shows, in accordance with a recent study [2], that insufflation of CO 2 into the abdominal cavity of pigs is associated with a substantial increase in blood flow in the peritoneum. Our findings also support the view that such vasodilation is caused by properties related to CO 2 itself, and not to changed central hemodynamics or activation of neural reflex mechanisms potentially elicited by increased intraabdominal pressure.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies reported higher ratios of tumour seeding-both peritoneal and at port sites-in laparoscopic surgeries 3,8,16,17 . Exposure to a pneumoperitoneum-laparoscopic environment is shown to enhance the invasive capacity of colonic adenocarcinomas by a protease-determined pathway 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, blood flow within the peritoneum may be influenced by insufflation with carbon dioxide. Such hyperemia could increase the propensity of implanted tumour cells to metastasize in these sites 16 . Tumour cells released into the operative field can therefore be made increasingly aggressive by a laparoscopic operative environment and can thus contribute to disease dissemination 8 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Two cytosolic enzymes ALT and AST are mostly used to evaluate hepatic function. In this study both the ALT and AST revealed no statistically significant changes among the different groups in respect to different time intervals.…”
Section: Effect Of Different Carbon Dioxide Pressure Gradients In Capmentioning
confidence: 99%